Liberdade pública e tripartição dos poderes no estado brasileiro: um enfoque filosófico a partir de G.W. Hegel - Yaçanã Eduarda da Cunha (2018)
This work aims to examining, in the juridical-sociological field, the principle of the Separation of Powers and their role as guarantor of public liberty in the Brazilian State, based on the it's philosophical view, brought by G.W. Hegel, and find out if there is in fact in the State (Social and) Democratic Brazilian rationality and public freedom. The object of study of this work, public liberty, was understood and used countless times in the most diverse contexts by the philosophical literature, yet no scholar or philosopher grasped its essence the concept, with as much mastery as Hegel did; with all its thorough study on Justice, Freedom and State, declared that it only exists as a rational constitution of the State. In this sense, public liberty is a concrete unit of the universal and the particular that rationally establishes the organization and the process of State functioning in connection with itself. To examine it in general and its particular specifications, it is necessary to think of it in connection with the whole. The present study starts from the hypothesis that, although the attributions of the different powers of the State are perfectly demarcated in the terms of its commission in the text of the Republican Constitution, the commitment of the rational public administration developed by the public freedom, permeated by disrespect for the principle of Separation of Powers, which depends not only on its nature, but also, on the mentality and procedure of the one who exercises the power. From the beginnings of constitutional history, one of the main functions of the Constitutions is the promotion of the individual freedom, which was permeated through the institution of the principle of Separation of Powers. Joining the role of State theorists, Hegel emerges with his studies declaring the State, in general, the realm of freedom, where every individual, complying his duty, is aware of the goal he seeks, and which the laws prescribe: the collective good, and lead a rational life where true freedom lies. In this way he brings to the principle of Separation of Powers another meaning beyond his representation of mechanical/instrumental artifice designed to prevent the dangers of abuses of power: rational form of political unity in the differentiation proper to modern social life, by which the particular spheres are brought back to the universal. In this way, the division of the powers of the State taken in its true sense is a guarantee of public liberty, for it is in it that the moment of rational determinism resides.